Inventory of Fish Species of the Bagridae Family in the Siak River, Siak District, Riau Province - Devi Dafiana; Roza Elvyra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Siak River is one of the main rivers in Riau Province which is a source of water for people living around it, both for household, fisheries, industrial and transportation purposes. In addition, the Siak River is also a habitat for various aquatic biota, one of which is fish species from the Bagridae family. This study aims to determine the number of fish species of the Bagridae family based on morphological characters in the waters of the Siak River, Riau Province. This research was conducted in December 2022-February 2023. The method used in this research is survey method. Identification of fish samples was carried out at the Zoology Laboratory, Department of Biology, Riau University. The results of the study found a total of 239 individuals from the Bagridae family consisting of 3 genus namely the genus Bagroides, Hemibagrus, Mystus, and 4 species namely Bagroides melapterus (29) individuals, Hemibagrus nemurus (143) individuals, Mystus nigriceps (55) individuals, and Mystus gulio (12) individuals. The most common Bagridae family fish species was Hemibagrus nemurus (60%), while the least common Bagridae family fish species was Mystus gulio (5%).